(Order of a Group). the Number of Elements of a Group (finite Or Infinite) Is Called Its Order

(Order of a Group). the Number of Elements of a Group (finite Or Infinite) Is Called Its Order

CHAPTER 3 Finite Groups; Subgroups Definition (Order of a Group). The number of elements of a group (finite or infinite) is called its order. We denote the order of G by G . | | Definition (Order of an Element). The order of an element g in a group G is the smallest positive integer n such that gn = e (ng = 0 in additive notation). If no such integer exists, we say g has infinite order. The order of g is denoted by g . | | Example. U(18) = 1, 5, 7, 11, 13, 17 , so U(18) = 6. Also, { } | | 51 = 5, 52 = 7, 53 = 17, 54 = 13, 55 = 11, 56 = 1, so 5 = 6. | | Example. Z12 = 12 under addition modulo n. | | 1 4 = 4, 2 4 = 8, 3 4 = 0, · · · so 4 = 3. | | 36 3. FINITE GROUPS; SUBGROUPS 37 Problem (Page 69 # 20). Let G be a group, x G. If x2 = e and x6 = e, prove (1) x4 = e and (2) x5 = e. What can we say 2about x ? 6 Proof. 6 6 | | (1) Suppose x4 = e. Then x8 = e = x2x6 = e = x2e = e = x2 = e, ) ) ) a contradiction, so x4 = e. 6 (2) Suppose x5 = e. Then x10 = e = x4x6 = e = x4e = e = x4 = e, ) ) ) a contradiction, so x5 = e. 6 Therefore, x = 3 or x = 6. | | | | ⇤ Definition (Subgroup). If a subset H of a group G is itself a group under the operation of G, we say that H is a subgroup of G, denoted H G. If H is a proper subset of G, then H is a proper subgroup of G. e is the trivial subgroup of G. If H = e and H G, H is called nontrivial. { } 6 { } Theorem (3.1 — One-Step Subgroup Test). Let G be a group and = 1 ; 6 H G. Then H is a subgroup of G if a, b H = ab− H (for additive notation,✓ a b H). 2 ) 2 Proof. − 2 Associativity of H derives from that of G. 1 [To show e H.] H = , so x H. Then xx− = e H by hypothesis. 2 6 ; 9 2 2 1 1 1 [To show x− H.] Also, ex− = x− H by hypothesis. 2 2 1 [To show H is closed.] Suppose x, y H. Then y− H and, by hypothesis, 1 1 2 2 xy = x(y− )− H. 2 Thus H G. ⇤ 38 3. FINITE GROUPS; SUBGROUPS Problem (Page 74 # 73). Let 2 2 H = a + bi a, b R, a + b = 1 . { | 2 } This is the set of points on the unit circle in the complex plane. Then H C⇤ under complex multiplication. Proof. 1 = 1 + 0i H since 12 + 02 = 1. 2 Suppose a + bi, c + di H. Then a2 + b2 = 1 and c2 + d2 = 1. 2 1 a + bi (a + bi)(c di) (a + bi)(c + di)− = = − = c + di (c + di)(c di) − ac + bd + bci adi − = (ac + bd) + (bc ad)i c2 + d2 − and (ac + bd)2 + (bc ad)2 = a2c2 + 2abcd + b2d2 + b2c2 2abcd + a2d2 = − − a2c2 + a2d2 + b2c2 + b2d2 = a2(c2 + d2) + b2(c2 + d2) = (a2 + b2)(c2 + d2) = 1 + 1 = 1, 1 so (a + bi)(c + di)− H. Thus H C⇤. 2 ⇤ Theorem (3.2 — Two-Step Subgroup Test). Let G be a group and = H G. Then H G if ; 6 ✓ (1) a, b H = ab H (closed under multiplication); 2 ) 2 1 (2) a H = a− H (closed under inverses). 2 ) 2 Proof. 1 1 Suppose a, b H. Then b− H by (2). By (1), ab− H, so H G by 2 2 2 Theorem 3.1. ⇤ 3. FINITE GROUPS; SUBGROUPS 39 Example. R360/n Dn. Proof. h i R360/n = R0, R360 , R2 360 , , R(n 1)360 h i n ·n · · · −n where Ri + Rj = R(i+j) mod 360n . o a 360 b 360 Let R , R R and suppose i = · and j = · . i j 2 h 360/ni n n Now a + b = qn + r, 0 r < n, so (a + b)360 (qn + r)360 r 360 i + j = = = q 360 + · . n n · n Then r 360 (i + j) mod 360 = · , 0 r < n, n so R mod 360 R . i+j 2 h 360/ni a 360 Now suppose R R , i = · . i 2 h 360/ni n a 360 n 360 a 360 (n a)360 360 i = 360 · = · − · = − , − − n n n so R360 i R360/n . Since − 2 h i Ri + R360 i = R360 mod 360 = R0 and R360 i + Ri = R360 mod 360 = R0, − − 1 R360 i = Ri− . Thus, by the Two-Step Subgroup Test, R360/n Dn. ⇤ − h i 40 3. FINITE GROUPS; SUBGROUPS Theorem (3.3 — Finite Subgroup Test). Let H be a finite nonempty subset of a group G. If H is closed under the operation of G, then H is a subgroup of G. Proof. 1 In view of Theorem 3.2, we need only show that a− H whenever a H. 2 2 1 If a = e, then a− = a, and we are done. So suppose a = e. 6 Consider the sequence a, a2, . By closure, each of these elements are in H. Since H is finite, not all of these elements are distinct. Suppose ai = aj, i > j. i j Then a − = e, and since a = e, i j > 1. Thus, 6 − i j 1 i j i j 1 1 aa − − = a − = e, so a − − = a− . i j 1 But i j 1 1, so a − − H and we are done. − − ≥ 2 ⇤ Suppose H G. To show H G, show any of the following: ✓ 6 (1) The identity is not in H. (2) an element of H whose inverse is not in H. 9 (3) two elements of H whose product is not in H. 9 Notation. Let G be a group, a G, and let 2 n a = a n Z . h i { | 2 } Note a0 = e. Theorem (3.4 — a is a Subgroup). h i Let G be a group and a G. Then a G. Proof. 2 h i Since a a , a = . Let an, am a . Then 2 h i h i 6 ; 2 h i n m 1 n m n m a (a )− = a a− = a − a , 2 h i so by Theorem 3.1, a G. h i ⇤ 3. FINITE GROUPS; SUBGROUPS 41 Example. In U(14), find 9 . h i 91 = 9, 92 = 81 = 11 mod 14, 93 = 99 = 1 mod 14. 1 1 Thus 9 = 1, 9, 11 with 9− = 11 and 11− = 9. h i { } Example. In D , R = R , R , R , R D . 4 h 270i { 0 90 180 270} 4 R270 + R270 = R180, R180 + R270 = R90, R90 + R270 = R0. Example. In Z15, 3 = 3, 6, 9, 12, 0 Z15. h i { } Recall here that an is na since the operation is addition modulo n. Definition (Center of a Group). The center, Z(G), lof a group G is the subset of elements of G that commute with every element of G: Z(G) = a G ax = xa x G . { 2 | 8 2 } Theorem (3.5 — Center is a Subgroup). Z(G) G. Proof. e Z(G), so Z(G) = . Suppose a, b Z(G). Then 2 6 ; 2 (ab)x = a(bx) = a(xb) = (ax)b = (xa)b = x(ab) x G, 8 2 so ab Z(G). 2 Now suppose a Z(G). Then ax = xa x G, so 2 8 2 1 1 1 1 1 1 1 1 a− (ax)a− = a− (xa)a− = (a− a)xa− = a− x(aa− ) = ) ) 1 1 1 1 exa− = a− xe = xa− = a− x. ) 1 Thus a− Z(G), and so Z(G) G by Theorem 3.2. 2 ⇤ 42 3. FINITE GROUPS; SUBGROUPS Problem (Page 75 # 79c). Let G = GL(2, R). Find Z(G). Solution. a b Suppose Z(G). Then c d 2 a b e f e f a b e f = GL(2, R) = c d g h g h c d 8 g h 2 ) ae + bg af + bh ae + cf be + df = e, f, g, h R eh fg = 0. ce + dg cf + dh ag + ch bg + dh 8 2 −3− − 6 Now ae + bg = ae + cf = bg = cf. ) For e = f = g = 1 and h = 0, eh fg = 1 = b = c. − − ) For e = g = h = 1 and f = 0, eh fg = 1 = b = 0 = c = 0. − ) ) Also, for e = h = 0 and f = g = 1, af + bh = be + df = af = df = a = d. ) ) a 0 Thus Z(G) = a = 0 . 0 a 6 ⇤ ⇢ Definition (Centralizer of a in G). Let a G, G a group. The centralizer of a in G is the set of all elements in G that comm2 ute with a: C(a) = g G ga = ag . { 2 | } Example. In D4, C(R ) = R , R , R , R = C(R ). 90 { 0 90 180 270} 270 C(R0) = D4 = C(R180). C(H) = R , H, R , V = C(V ). { 0 180 } C(D) = R , D, R , D0 = C(D0). { 0 180 } Thus Z(D ) = R , R . 4 { 0 180} 3. FINITE GROUPS; SUBGROUPS 43 Theorem (3.6 — C(a) is a Subgroup). For each a in a group G, C(a) G. Proof. Will be assigned as homework (Page 72 # 41). Similar to the proof of Theorem 3.5. ⇤ 1 1 Problem (Page 75 # 79a). Let G = GL(2, ). Find C . R 1 0 Solution. ✓ ◆ a b 1 1 Let C . Then c d 2 1 0 ✓ ◆ 1 1 a b a b 1 1 a + c b + d a + b a = = = = 1 0 c d c d 1 0 ) a b c + d c ) b = c and a = b + d = d = a b.

View Full Text

Details

  • File Type
    pdf
  • Upload Time
    -
  • Content Languages
    English
  • Upload User
    Anonymous/Not logged-in
  • File Pages
    10 Page
  • File Size
    -

Download

Channel Download Status
Express Download Enable

Copyright

We respect the copyrights and intellectual property rights of all users. All uploaded documents are either original works of the uploader or authorized works of the rightful owners.

  • Not to be reproduced or distributed without explicit permission.
  • Not used for commercial purposes outside of approved use cases.
  • Not used to infringe on the rights of the original creators.
  • If you believe any content infringes your copyright, please contact us immediately.

Support

For help with questions, suggestions, or problems, please contact us